Infant Central Nervous System Aspergillosis with First-episode of Intracranial Hemorrhage: A case report. Issue 47 (November 2017) - Wang, Yang; Li, Deyuan; Qiao, Lina; Zhao, Fumin
Abstract: Rationale: Central nervous system (CNS) aspergillosis has the characteristics of multifocality, polymorphism, and coexistence of pathological types, and missed diagnosis and misdiagnosis frequently occur at the initial stage. The thesis reports a rare case of infant infection of CNS aspergillosis with the first-episode of intracranial hemorrhage. Patient concerns: An 11-month-old female infant suffered convulsion and coma two days after the onset of fever and emesis. Its cranial computed tomography (CT) displayed subdural hemorrhage in the left tentorium cerebelli and tests indicated normal cerebrospinal fluid (CSF). Three days after being hospitalized, the infant had difficulty breathing and its CT presents consolidation in the right lung. However, treatment with ceftriaxone (ivgtt) had no effect on the baby. Diagnosis: The patient's bronchoalveolar lavage fluid (BALF) was cultured into Aspergillus spp, its galactomannan (GM) antigen in CSF counted 3.0, higher than that in BALF which counted 2.6, and cranial magnetic resonance imaging (MRI) revealed multiple ring reinforced tubercles in sulci. Hence it was clinically diagnosed with CNS aspergillosis. Interventions: Voriconazole for intravenous injection. After the intravenous injection, its trough concentration was 4.2 μg/mL, and it was within the recommended range. Outcomes: After one week's treatment with voriconazole, the infant's consciousness was improved. Four weeks later, with normothermia and clear consciousness, the patient was discharged. With oral administration of voriconazole up to 16 weeks, its physical state suggests no relapse and cranial MRI indicated disappearance of nodules in sulci. Lessons: CNS aspergillosis with first-episode of intracranial hemorrhage probably leads to misdiagnosis and GM test combined with cranial MRI can augment its accuracy in the early diagnosis.